2021
DOI: 10.1055/s-0041-1740149
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Coagulation Abnormalities of Autoimmune Acquired Factor V Deficiency with a Focus on Japan

Abstract: Coagulation factor V (or FV for the purpose of medical safety) is an essential cofactor of coagulation factor X in the common pathway of coagulation; severe FV deficiency leads to a bleeding tendency. Although both congenital and acquired FV deficiencies are widely recognized, FV deficiency also presents as an autoimmune disorder. A nationwide survey on autoimmune coagulation factor deficiencies (AiCFDs) conducted in Japan by our Japanese Collaborative Research Group identified 24 new patients with autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 38 publications
1
63
0
Order By: Relevance
“…Furthermore, since there is no compartment syndrome, the chance of receiving emergency medical care may be less than that of other AiCFDs. Moreover, 15% (6/40 cases) of cases had no bleeding symptoms, which was approximately half to that of AiFVD 27 and twice that of AiFXD. 28 The average number of bleeding events per patient was 1.6, which was approximately one-half that of AiFVD and nearly the same as AiFXD (2.0 per patient).…”
Section: Bleeding Sites or Symptoms And Severitymentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, since there is no compartment syndrome, the chance of receiving emergency medical care may be less than that of other AiCFDs. Moreover, 15% (6/40 cases) of cases had no bleeding symptoms, which was approximately half to that of AiFVD 27 and twice that of AiFXD. 28 The average number of bleeding events per patient was 1.6, which was approximately one-half that of AiFVD and nearly the same as AiFXD (2.0 per patient).…”
Section: Bleeding Sites or Symptoms And Severitymentioning
confidence: 90%
“…3A), which is also evidently different from other AiCFD. 27,28 Bleeding Sites or Symptoms and Severity…”
Section: Underlying Diseases/conditionsmentioning
confidence: 99%
“…3 c) [ 3 ]. Thus, the patient was ‘definitely diagnosed’ with AiFVD in accordance with the diagnostic criteria enacted by the Japanese Ministry of Health, Labor, and Welfare [ 2 , 4 ]. Factor V inhibitor and anti-factor V autoantibodies were not detected on day 73 and 94, likely because of antibody eradication treatment using PSL alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, immunological remission was confirmed on days 73 by the absence of anti-factor V autoantibodies on ELISA and factor V inhibitor. We previously reported that 73% of Japanese patients with AiFVD initially received PSL for antibody eradication, while 13.5% patients received a pulse PSL regimen, with success rates of 74.7% and 70.8%, respectively [ 2 ]. The success rate of PSL alone (85.1%) is higher than that of overall PSL (74.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation